Incidence of seroma in abdominoplasty with versus without the use of drains and quilting sutures: a systematic review and meta-analysis - Katrienne Guidolini Martinelli; Caroline Ferraz Rezende; Felipe Gama e Colombo; Katrini Guidolini Martinelli (Revista Brasileira de Cirurgia Plástica)
Introduction: Abdominoplasty, which aims to improve body contour, has been upgraded by its association with limited dissection of the cutaneous flap and quilting sutures in the same surgery to avoid the formation of postabdominoplasty seroma, a complication that troubles both patient and surgeon. Therefore, this study aimed to assess whether the use of quilting sutures is associated with a lower incidence of seroma after abdominoplasty than the use of drains. Methods: A systematic review of the literature and a meta-analysis were performed of the Science Direct, Scielo, Pubmed, Lilacs, CINAHL, and Scopus databases. The data analysis was performed using the Stata 12.0 program and the I2 statistic proposed by Higgins, with a 95% confidence interval for the relative risk for seroma by intervention type (drain, quilting sutures, drain with quilting sutures). The study was registered in PROSPERO (CRD42019120399). Results: Five studies met the inclusion criteria and were included in the meta-analysis. Quilting sutures showed a protective effect (versus use of drain with quilting sutures) in the prevention of seroma (relative risk, 0.13; 95% confidence interval, 0.02-0.66). Conclusion: These findings suggest that the use of quilting sutures instead of drains in abdominoplasty can effectively prevent seroma formation.